UZBEKISTAN - NATIONAL VALUES APPRECIATED COUNTRY - Qiyam Nazarov (Scholar Express Journal, 2024)
In recent years, when New Uzbekistan is being rapidly built in our country, fundamental reforms are being carried out in the sphere of appreciation of universal human values, as well as in all aspects of the life of our society.
Keywords: Universal Human Values; Society